Long-Chain Omega-3 Fatty Acids Eicosapentaenoic Acid and Docosahexaenoic Acid and Blood Pressure: A Meta-Analysis of Randomized Controlled Trials - Miller, Paige E.; Van Elswyk, Mary; Alexander, Dominik D. (American journal of hypertension, 2014)
Abstract BACKGROUND Although a large body of literature has been devoted to examining the relationship between eicosapentaenoic and docosahexaenoic acids (EPA+DHA) and blood pressure, past systematic reviews have been hampered by narrow inclusion criteria and a limited scope of analytical subgroups. In addition, no meta-analysis to date has captured the substantial volume of randomized controlled trials (RCTs) published in the past 2 years. The objective of this meta-analysis was to examine the effect of EPA+DHA, without upper dose limits and including food sources, on blood pressure in RCTs. METHODS Random-effects meta-analyses were used to generate weighted group mean differences and 95% confidence intervals (CIs) between the EPA+DHA group and the placebo group. Analyses were conducted for subgroups defined by key subject or study characteristics. RESULTS Seventy RCTs were included. Compared with placebo, EPA+DHA provision reduced systolic blood pressure (−1.52mm Hg; 95% confidence interval (CI) = −2.25 to −0.79) and diastolic blood pressure (−0.99mm Hg; 95% CI = −1.54 to −0.44) in the meta-analyses of all studies combined. The strongest effects of EPA+DHA were observed among untreated hypertensive subjects (systolic blood pressure = −4.51mm Hg, 95% CI = −6.12 to −2.83; diastolic blood pressure = −3.05mm Hg, 95% CI = −4.35 to −1.74), although blood pressure also was lowered among normotensive subjects (systolic blood pressure = −1.25mm Hg, 95% CI = −2.05 to −0.46; diastolic blood pressure = −0.62mm Hg, 95% CI = −1.22 to −0.02). CONCLUSIONS Overall, available evidence from RCTs indicates that provision of EPA+DHA reduces systolic blood pressure, while provision of ≥2 grams reduces diastolic blood pressure.